abx 2 + (b 2 - ac)x - bc = 0
abx 2 + b 2 x - acx - bc = 0
bx(ax + b) â c(ax + b) = 0
(ax + b)(bx â c) = 0
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
RELATED QUESTIONS :
Draw the graph ofNCERT - Mathematics